PENANAMAN NILAI KARAKTER DAN NILAI – NILAI PANCASILA MELALUI MATA PELAJARAN PPKN PADA SISWA KELAS VIII-1 SMP NEGERI 1 TORGAMBA - Budi Winata Hasibuan (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This study aims to determine the process of planting the values of character and values of Pancasila in class VIII-1 students through PPKn subjects in Torgamba 1 Public Middle School, Labuhanbatu Selatan Regency. The method in this study using descriptive qualitative research. Technique analysis of data in this study using interviews, observations, and documentation.The results of the study showed that the Process of character value and Pancasila values had been carried out according to the expected values of students' character. Through PPKn subjects, the teachers have instilled these values, starting with the syllabus, RPP and learning process in the classroom as expected. This research is an effort made by PPKn Teachers in fostering the value of character and values of Pancasila through PPKn learning in class VIII-1 has gone well.